Institucionalización de las instituciones políticas y su impacto sobre las políticas públicas - Carlos Scartascini; Mariano Tommasi (Inter-American Development Bank (IDB), 2012)
– This paper argues that institutionalization is an equilibrium phenomenon and is associated with better policies and better results in terms of economic development. In support of this argument is presented a theoretical model that extends the space of feasible actions for political actors, including the possibility of investing in both institutionalized and non-institutionalized arenas. Thus, to visualize the process of institutionalization can be endogenous to the functioning of political institutions. In addition to this conceptual model, quantitative results are presented which show that low levels of institutionalization tend to weaken the results arising from the literature of more traditional political economy. That is, low institutionalization in the context of traditional political institutions, particularly those jure measures may not be relevant in explaining policy outcomes. Still, this work opens up more questions than it answers and leaves lines of research proposals that can help provide answers to them.
Keywords: D72; D73; D78; 330